Evaluation Study of Power Requirements Planning in Electrical Installations in the Construction of the Pagedangan Tangerang Overpass Bridge - Ramza, Harry; Akbar, Januar; Machdi, Agustini Rodiah; Sofwan, Agus (Universitas Mandiri, 2024)
The Pagedangan Tangerang Overpass Bridge is one of the transportation infrastructure in the Tangerang area. The installed electrical loads include lighting loads (lamps) and power loads (which of course require a fairly large electrical power supply. The electrical power installed on the Pagedangan Overpass Bridge is 20,300 W. The power supplied from PLN is 33,000 VA from PLN and the total power capacity of the transformer is 37,500 VA. The results of the drop voltage analysis calculation for the PJU lighting load are 5,530 VA. For the analysis results of the drop voltage of 2.00 V, the voltage drop percentage is 0.42% and the conductor power loss is 12.12 W, the power loss percentage is 0.27%.